運用原則取向知識翻新活動促進師資生對話與教學觀 - 楊珊瑜(Shan-Yu Yang); 陳美如(Mei-Ju Chen) (Jiao yu yu xin li yan jiu, 2024)
Learning science recognizes varied definitions of learning, evolving from mere knowledge acquisition to encompass deep understanding, collaborative knowledge sharing, community engagement, and creative thought. In the era of the Internet, it is even more crucial to invest in environmental cooperation to foster knowledge creation. This study investigates Knowledge Building (KB) among a community of student teachers in a teacher training curriculum, which focuses on KB principles. The researcher uses Knowledge Forum (KF) as a collaborative tool to facilitate this study. This study aims to aid the development of student teachers in teaching practice and to explore the process of their discourse and teaching perspectives. This study adopted case study approach with 47 student teachers who took a university course titled “Teaching Principles” over one semester. The findings indicated: (1) Principle based KB activities facilitate student teachers’ discourse progress. (2) Guided by the KB principles, although arguin